2014
DOI: 10.4049/jimmunol.1303479
|View full text |Cite
|
Sign up to set email alerts
|

miR-190b Is Markedly Upregulated in the Intestine in Response to Simian Immunodeficiency Virus Replication and Partly Regulates Myotubularin-Related Protein-6 Expression

Abstract: HIV replication and the cellular miRNA machinery interconnect at several post-transcriptional levels. To understand their regulatory role in the intestine, a major site of HIV/SIV replication, dissemination and CD4+ T cell depletion we profiled miRNA expression in colon following SIV infection (10-Acute-SIV, 5-uninfected). Nine (4-up and 5-down) miRNAs showed statistically significant differential expression. Most notably, miR-190b expression showed high statistical significance (Adjusted p=0.0032), the greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 63 publications
4
40
0
Order By: Relevance
“…For instance, several in vitro studies have shown altered miRNA expression in response to HIV infection (30)(31)(32)(33)(34), and recent miRNA profiling studies performed on brain (35) and plasma samples (36) provide strong evidence of their dysregulation during SIV infection. In addition, we recently reported miR-190b to be significantly upregulated in the intestine at all stages of SIV infection (37) and that viral replication rather than infection-related inflammatory responses induced miR-190b upregulation (37). Further, we also confirmed MTMR6, a PIP3 phosphatase and an inhibitor of CD4 ϩ T cell proliferation and activation, to be a direct miR-190b target (37).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…For instance, several in vitro studies have shown altered miRNA expression in response to HIV infection (30)(31)(32)(33)(34), and recent miRNA profiling studies performed on brain (35) and plasma samples (36) provide strong evidence of their dysregulation during SIV infection. In addition, we recently reported miR-190b to be significantly upregulated in the intestine at all stages of SIV infection (37) and that viral replication rather than infection-related inflammatory responses induced miR-190b upregulation (37). Further, we also confirmed MTMR6, a PIP3 phosphatase and an inhibitor of CD4 ϩ T cell proliferation and activation, to be a direct miR-190b target (37).…”
supporting
confidence: 61%
“…In addition, we recently reported miR-190b to be significantly upregulated in the intestine at all stages of SIV infection (37) and that viral replication rather than infection-related inflammatory responses induced miR-190b upregulation (37). Further, we also confirmed MTMR6, a PIP3 phosphatase and an inhibitor of CD4 ϩ T cell proliferation and activation, to be a direct miR-190b target (37).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Lately, the enhanced expression of miR-21 (13) and miR-142 (14) was correlated with macrophage activation and encephalitis in the brain of SIV-infected rhesus macaques. Focusing on the GI tract, an important site of CD4 ϩ T-cell depletion and HIV/SIV replication, we (15,16) and others (17) reported significant miRNA dysregulation in intact colon during SIV infection. Unlike our two previous studies that utilized intact intestinal tissue (15,16), in the present study, we focused exclusively on the intestinal lamina propria compartment to obtain a deeper understanding of the link between aberrant miRNA expression and chronic immune activation/inflammation in the intestine.…”
mentioning
confidence: 99%
“…Focusing on the GI tract, an important site of CD4 ϩ T-cell depletion and HIV/SIV replication, we (15,16) and others (17) reported significant miRNA dysregulation in intact colon during SIV infection. Unlike our two previous studies that utilized intact intestinal tissue (15,16), in the present study, we focused exclusively on the intestinal lamina propria compartment to obtain a deeper understanding of the link between aberrant miRNA expression and chronic immune activation/inflammation in the intestine. In tune with this objective, we collected serial intestinal resection segments from the same animals before and at 21, 90, and 180 dpi and separated the different mucosal compartments (epithelium, intraepithelial lymphocytes, lamina propria leukocytes [LPLs], and fibrovascular stroma).…”
mentioning
confidence: 99%